Understanding simple module of some group algebras and path algebras - Aw, Wee Chong (Nanyang Technological University, 2021)
Group algebra uses the structure of groups and brings it to the field of module theory. This allow us to use another theory to understand the groups. The question is how well do we understand the modules of the group algebras. We attempt to dive into the simple modules given by the group algebra and hope to identify and study them. Furthermore, we dive into path algebras to obtain interesting results.